Enhancing photosynthesis and root development for better fruit quality, aroma, and lessening of radioactive materials in key lime (Citrus aurantifolia) using Trichoderma harzianum and Bacillus thuringiensis - Salem, Abdelmoaty (Elsevier Masson, 2024)
The present study was conducted to investigate the effects of Trichoderma harzianum and Bacillus thuringiensis alone or with gradual levels of NPK on photosynthesis, growth, fruit quality, aroma improvement and reduced radionuclides of key lime fruits. The lemon seedlings were treated with (T0) without fertilizers as control, (T1) 100g of NPK at 100, (T2) 5 g of Trichoderma. harzianum at 50 + 50 g of NPK at 50, (T3) 5 g of Bacillus thuringiensis at 50 + 50 g of NPK at 50 , (T4) 7.5 g of Trichoderma harzianum at 75 + 25 g of NPK at 25 , (T5) 7.5 g of Bacillus thuringiensis at 75 + 25 g of NPK at 25 , (T6) 10 g of Trichoderma harzianum at 100 and (T7)10 g of Bacillus thuringiensis at 100 . The results showed that T2 increased net photosynthetic rate, stomatal conductance, transpiration rate, internal CO2 concentration, fresh and dry root biomass by 209, 74, 56, 376, 69.4 and 71.6, while, T5 increased root volume, root length, and root tip number by 27.1, 167, and 67, respectively over the control trees. The microbial treatments developed cortex, vascular cylinder and tracheal elements of the root. Fruit number, length, diameter, weight, pulp thickness, pulp/peel ratio, juice, total soluble solids (TSS), pigment contents and antioxidant activity increased significantly in the T2 treatment. Vitamin C, total phenols, total flavonoids, and total sugar content increased by 1.59-, 1.66-, 1.44- and 2.07- fold in T5 treated fruits compared to the control. The two microbes increased volatile compounds and decreased radionucleotides in the fruit, moreover, 27 identified and 2 (two) unmatched volatile compounds were identified by GCMS analysis. It is concluded that T. harzianum and B. thuringiensis with 25–50 g NPK treatments improved photosynthesis, root structure, fruit growth, fruit quality, aroma and lessened radionuclides in key lime fruits.